The Role of Kutub As-Sittah in Verifying the Authenticity of Hadith: A Takhrij Science Approach - Syam, Nur Fadhilah; Nurwandri, Andri (Jurnal Penelitian Medan Agama, 2024)
The concept of takhrij hadith, a critical process in Islamic hadith science which aims to investigate and verify the sanad (chain of narrators) and matan (text) of hadith from the original source. Takhrij allows scholars to determine the authenticity and validity of a hadith by analyzing primary sources such as al-Kutub As-Sittah. This study is important in determining the quality of a hadith, whether sahih, hasan, or daif, as well as classifying the source as marfu', mawquf, or maqtu'. The existence of takhrij is very helpful in understanding the historical context and depth of spirituality contained in the hadith of the Prophet Muhammad SAW. by investigating, comparing, and interpreting various narrations from books such as Sahih al-Bukhari, Sahih Muslim, and Sunan Abu Daud. Thus, the takhrij hadith not only provides a deeper understanding of Islamic teachings, but also plays an important role in maintaining the integrity and authenticity of the Muslim religious traditions.